ANALISIS PENDAPATAN USAHATANI SAWI DI DESA PETLENG KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Emirensiana Latuan; Nerci W Mapada (Politeknik Pertanian Negeri Kupang, 2021)
To get maximum income, farming must be able to increase production and reduce production costs. The research sample used the Slovin formula so that the number of samples was 50 mustard farmers. To determine the income of mustard farming and to find out whether mustard farming in Petleng Village, North Central Alor Regency is feasible or not to be developed. The data obtained were analyzed using the income formula: = TR –TC and the farming feasibility formula: R/C Ratio = TR/TC. average Total Cost Rp. 788,200, the average income is Rp. 3,740,000 and the average farm income is Rp. 2,951,800, and the R/C of mustard farming in Petleng Village is greater than 1, which is 4.74, this means that mustard farming in Petleng Village is feasible to develop. Key Words: income, eligibility, mustard, Petleng